-6a(a-3)=-5(3a-1)-5

Simple and best practice solution for -6a(a-3)=-5(3a-1)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6a(a-3)=-5(3a-1)-5 equation:


Simplifying
-6a(a + -3) = -5(3a + -1) + -5

Reorder the terms:
-6a(-3 + a) = -5(3a + -1) + -5
(-3 * -6a + a * -6a) = -5(3a + -1) + -5
(18a + -6a2) = -5(3a + -1) + -5

Reorder the terms:
18a + -6a2 = -5(-1 + 3a) + -5
18a + -6a2 = (-1 * -5 + 3a * -5) + -5
18a + -6a2 = (5 + -15a) + -5

Reorder the terms:
18a + -6a2 = 5 + -5 + -15a

Combine like terms: 5 + -5 = 0
18a + -6a2 = 0 + -15a
18a + -6a2 = -15a

Solving
18a + -6a2 = -15a

Solving for variable 'a'.

Reorder the terms:
18a + 15a + -6a2 = -15a + 15a

Combine like terms: 18a + 15a = 33a
33a + -6a2 = -15a + 15a

Combine like terms: -15a + 15a = 0
33a + -6a2 = 0

Factor out the Greatest Common Factor (GCF), '3a'.
3a(11 + -2a) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(11 + -2a)' equal to zero and attempt to solve: Simplifying 11 + -2a = 0 Solving 11 + -2a = 0 Move all terms containing a to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -2a = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -2a = 0 + -11 -2a = 0 + -11 Combine like terms: 0 + -11 = -11 -2a = -11 Divide each side by '-2'. a = 5.5 Simplifying a = 5.5

Solution

a = {0, 5.5}

See similar equations:

| -7.87+.23x=31 | | ax^2-3x+5=0 | | 11x+5=8x+23whatisx | | -7.87+.23x=38.13 | | 3(4x-3)-8=4+2x | | 3v+27=24 | | A-0.3A=95 | | 10w-7w=27 | | 101x=5 | | 5(n-12)-24=3(n+2) | | -8=7h+20 | | -2(y+2)=-16 | | h=-4.9t^2+vt | | 9r+10=118 | | A-0.1A=85 | | 5000+5x=6650 | | -3-2-4= | | 23=2+7x | | -3-2+-4= | | 2a+6-5a=4a+10 | | 20+10(a-4)=8a+2 | | 11a=6 | | -3+2-4= | | -42+5k=k-2k | | -24x^2+32= | | -50+.50x=153.50 | | -50+.50x=300 | | -18x-9=x-17 | | -3+2+-4= | | -3+2+4= | | 4y+9=29 | | 6-8x-10x-15=x-17 |

Equations solver categories